Prospects for Introduction of Robotics in Service - Sotnik, S.; Lyashenko, V. (International Journal of Academic Engineering Research, 2022)
The paper reviews promising robotic devices in service. 6 options for robots use for various purposes were considered, ranging from autonomous drones for food delivery to exoskeleton for installation operators. The aim of this work is to provide an overview of evolution of research in robotics ranging from humanoid robot to modern devices that allow you to preserve human health during heavy physical labor. Trend trends in service robotics are considered because of their common goal to bring robots closer to human social needs.
Keywords: robotics; implementation